Activation of NF-κB in basolateral amygdala is required for memory reconsolidation in auditory fear conditioning. - Jijian Si; Jianli Yang; Lifen Xue; Chenhao Yang; Yixiao Luo; Haishui Shi; Lin Lu (PLoS ONE, 2012)
Posttraumatic stress disorder (PTSD) is characterized by acute and chronic changes in the stress response, manifested as conditioned fear memory. Previously formed memories that are susceptible to disruption immediately after retrieval undergo a protein synthesis-dependent process to become persistent, termed reconsolidation, a process that is regulated by many distinct molecular mechanisms that control gene expression. Increasing evidence supports the participation of the transcription factor NF-κB in the different phases of memory. Here, we demonstrate that inhibition of NF-κB in the basolateral amygdala (BLA), but not central nucleus of the amygdala, after memory reactivation impairs the retention of amygdala-dependent auditory fear conditioning (AFC). We used two independent pharmacological strategies to disrupt the reconsolidation of AFC. Bilateral intra-BLA infusion of sulfasalazine, an inhibitor of IκB kinase that activates NF-κB, and bilateral intra-BLA infusion of SN50, a direct inhibitor of the NF-κB DNA-binding complex, immediately after retrieval disrupted the reconsolidation of AFC. We also found that systemic pretreatment with sodium butyrate, a histone deacetylase inhibitor that enhances histone acetylation, in the amygdala rescued the disruption of reconsolidation induced by NF-κB inhibition in the BLA. These findings indicate that NF-κB activity in the BLA is required for memory reconsolidation in AFC, suggesting that NF-κB might be a potential pharmacotherapy target for posttraumatic stress disorder.